Using multiple versions of speech input in phone recognition - Liberman, Mark; Yuan, Jiahong; Stolcke, Andreas; Wang, Wen; Mitra, Vikramjit (Proc. IEEE ICASSP, 2013)
This study investigates the use of multiple versions of the same speech unit in automatic phone recognition. Two methods were applied to combine multiple utterance versions in decoding: cross forced-alignment and n-best ROVER. The phone error rate was reduced from 15% to 2% on isolated words and from 33% to 19% on TIMIT sentences. The error rate was reduced the most when the second version was added, and less so as each additional version was added. Depending on the language model weight, it might be better to use the language model only in n-best generation, but omit it in scoring the hypotheses applied to the combination methods. N-best ROVER effectiveness may be enhanced by lowering the language model weight.